Online Class UI/UX Design Using Design Thinking Method in Virtual Reality Environment - Bosya Perdana; Tata Sutabri (International Journal of Information Engineering and Science, 2024)
Online learning has become an essential component of modern education; however, conventional online learning platforms often rely on two-dimensional interfaces that limit user engagement, interaction, and immersion. These limitations reduce learning motivation and hinder the creation of an effective learning experience, particularly for activities that require active participation. To address these challenges, this research focuses on the design of User Interface (UI) and User Experience (UX) for online learning implemented in a Virtual Reality (VR) environment. The objective of this study is to develop a user-centered VR-based online learning interface that enhances interaction, usability, and learning comfort. This research applies the Design Thinking methodology, which consists of five stages: empathize, define, ideate, prototype, and test. User needs and usability issues were identified through observations and interviews, followed by interface design and prototype development of a VR learning environment featuring chat rooms, whiteboards, slide presentations, and virtual representations of teachers and students. Usability evaluation was conducted using the Maze platform to measure user success rates in completing predefined tasks. The results show that 80% of users completed tasks through the expected interaction paths, exceeding the minimum usability threshold of 70%, while 20% of users failed to complete the tasks, indicating areas for improvement. These findings demonstrate that the proposed UI/UX design effectively supports user interaction and usability in a VR-based learning environment. In conclusion, this study confirms that integrating Design Thinking into the UI/UX design process contributes to the development of effective and user-centered VR-based online learning systems, while also highlighting the importance of usability evaluation for refining immersive educational interfaces.